Strengthening Spiritualism in Andragogical Education Through Majlis Taklim Sarwe’en Sabilul Muttaqin in Probolinggo City - Aimmah, Agus Nashihul; Hidayah, Ulil (IJLHE: International Journal of Language, Humanities, and Education, 2024)
The aim of this research is to expand knowledge on reinforcing spiritual values among congregation members within the framework of andragogical education at Majelis Taklim Sarwe’en Sabilul Muttaqin in Curahgrinting Village, Kanigaran District, Probolinggo City. Enhancing spirituality through education is essential for individuals. This study successfully engaged participants from various social strata. Majelis Taklim encompasses all activities of the Muslim community related to Islamic education and teaching, irrespective of the gender or social status of its members. Moreover, these activities are not restricted by location or time of implementation. This research employs a qualitative approach, utilizing descriptive qualitative research methods. Data collection techniques include observation, interviews, and documentation to capture the phenomena related to the research objects, as well as recording the conditions and locations involved. Source triangulation is incorporated through interviews with Kyai Mahmud Said and other educators (Asatidz). The findings reveal that spirituality among the community of Majelis Taklim Sarwe’en Sabilul Muttaqin is evident not only in worship practices but also in all aspects of their social lives. Loving interactions, a spirit of mutual cooperation, and the preservation of religious traditions reflect their spiritual depth. Each individual supports others in the collective pursuit of happiness in this world and the hereafter